The Effect of Service Performance on Visitor Satisfaction and Loyalty in Mojosemi Forest Park Agrotourism, Magetan Regency - Damar Prakoso; Taufik Setyadi; Ika Sari Tondang (Universitas Muhammadiyah Palembang, 2026)
The relationship between service performance, visitor satisfaction, and loyalty has become a crucial element in strengthening sustainable agrotourism destinations. Mojosemi Forest Park, located in Magetan Regency, was selected as the research site due to its natural attractions and the challenges it faces in retaining visitor satisfaction and loyalty amid growing competition. A quantitative approach was employed with data collected from 100 respondents using questionnaires, and the analysis was conducted through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that service performance positively and significantly affects satisfaction, while satisfaction strongly influences loyalty. Service performance also exerts a direct effect on loyalty, with satisfaction confirmed as a partial mediator in the relationship. These findings highlight that improvements in the SERVQUAL dimensions—reliability, assurance, tangibles, empathy, and responsiveness—not only enhance the visitor experience but also strengthen long-term loyalty. The academic contribution of this study lies in expanding the literature on satisfaction’s mediating role in linking service performance and loyalty within the context of Indonesian agrotourism. From a practical perspective, the results provide valuable insights for managers of Mojosemi Forest Park to design service strategies that ensure sustainable improvements, enhance visitor engagement, and reinforce destination competitiveness in the modern tourism industry